PELESTARIAN JENIS MERBAU (Intsia spp.) BERBASIS ASOSIASI DAN DISTRIBUSI SPASIAL DI HUTAN TAMAN WISATA ALAM GUNUNG MEJA MANOKWARI - , EZROM BATORINDING ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Merbau (Intsia spp.) is a wood species widely used and of high economic value. Until now wood supply is still fulfilled by deforestation, therefore it is feared that the impact will threaten its availability in nature. Along with the rapidly growing development, if this type of exploitation is continuously done without any conservation efforts made to counterbalance it, it might result in the declining of its number in nature. This study aims at determining the tree species associated with merbau, understanding the distribution pattern of merbau and identifying merbauâs diameter increment in the lowland forests of Gunung Meja Natural Tourism Park Manokwari West Papua to support its conservation efforts. 1,1% sampling intensity (IS) was used to determine the location of the research. The research was conducted by making 5 observation plots, each of which was 100m x 100m. On each observation plot, smaller plots of 10m x 10m were continuously placed. The total number of observation plots was 500 plots. Observation was done on all vegetation of > 10 cm in diameter. Association analysis (Chi-square test) and index of dispersion (ID) using d-parameter was peformed to determine the distribution associations and patterns of Intsia . Mean annual increment (MAI) was calculated from the increment. The results showed that Intsia tends to positively associate with the dominant species in the forests of Gunung Meja Natural Tourism Park. The spatial distribution patterns tend to follow a random pattern and Intsiaâs diameter increment in lowland forests on Gunung Meja Natural Tourism Park tend to be smaller than Intsiaâs diameter increment in some forest plants, which amounted to 0.39 cm per year and 0.82 cm per year.